2017
DOI: 10.6018/eglobal.16.2.249241
|View full text |Cite
|
Sign up to set email alerts
|

Qualidade de vida e morbidade referida de mulheres produtivamente ativas

Abstract: Introducción: Morbilidad referida, hábitos de vida y calidad de vida es una tríada que parece estar alineada y ha sido poco explorada en el contexto de vida de las mujeres. <br /><br />Este estudio tuvo como objetivo verificar el índice de calidad de vida de mujeres productivamente activas y asociarlo con la morbilidad referida y hábitos de vida. <br /><br />Método: Estudio descriptivo, analítico, transversal. La muestra se constituyó de 121 mujeres que trabajan en una institución de sa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 11 publications
1
11
1
7
Order By: Relevance
“…The general quality of life of WHML servers was from regular to good, with an average of 65.62 (±12.45). This score is similar to the study on the quality of life of female hospital workers in São Paulo, whose average was 64.4 (±12), 24 but the respondents had associated morbidities. Among emergency room workers, the overall average quality of life was lower 53.62 (±21.36).…”
Section: Job Satisfaction Quality Of Lifesupporting
confidence: 85%
See 2 more Smart Citations
“…The general quality of life of WHML servers was from regular to good, with an average of 65.62 (±12.45). This score is similar to the study on the quality of life of female hospital workers in São Paulo, whose average was 64.4 (±12), 24 but the respondents had associated morbidities. Among emergency room workers, the overall average quality of life was lower 53.62 (±21.36).…”
Section: Job Satisfaction Quality Of Lifesupporting
confidence: 85%
“…9 The results obtained in the WHML for this domain were similar to those of workers of a hospital in the Southeast of Brazil, whose participants had musculoskeletal symptoms, which may influence the autonomy and independence to perform daily activities, at work or home. 24 In the other direction, the most highly rated domain in the present study was social relations, with an average of 70.31 (±16.38). This domain involves personal relationships inside and outside work, family support, and social relationships in general.…”
Section: Job Satisfaction Quality Of Lifementioning
confidence: 61%
See 1 more Smart Citation
“…Conversely, a study conducted with women prisoners in Ceará showed different results, since the majority of the women had undergone preventive exams within the previous year. 16 The QoL scores of the detainees, overall and in the different domains, were lower than those identified in other studies [25][26][27][28][29] that used the same instrument. When comparing the results of the present study with those of studies carried out with healthy women, or even with women affected by serious illnesses, the inmates' QoL mean scores were significantly lower, demonstrating the negative impact of the prison situation on the women's lives.…”
Section: Discussioncontrasting
confidence: 53%
“…The mean of the overall QoL of the inmates was 46, while the mean was not lower than 55.2 in any other study, with the same trend for the domain scores. [25][26][27][28][29] Prison influenced the women's perception of their QoL, with significantly negative results for those that reported health problems and that lacked or had impaired sleep.…”
Section: Discussionmentioning
confidence: 99%